An in‐house protocol for improved flood field calibration of TrueBeam FFF cine imaging. (January 2017) - Faught, Austin M.; Yin, Fang‐Fang; Adamson, Justus
Abstract: Purpose: TrueBeams equipped with the 40 × 30 cm 2 Electronic Portal Imaging Devices (EPIDs) are prone to image saturation at the image center when used with flattening filter free (FFF) photon energies. While cine imaging during treatment may not saturate because the beam is attenuated by the patient, the flood field calibration is affected when the standard calibration procedure is followed. Here, we describe the hardware and protocol to achieve improved image quality for this model of TrueBeam EPID. Materials & methods: A stainless steel filter of uniform thickness was designed to have sufficient attenuation to avoid panel saturation. The cine imaging flood field calibration was acquired with the filter in place for the FFF energies under the standard calibration geometry (SID = 150 cm). Image quality during MV cine was assessed with & without the modified flood field calibration using a low contrast resolution phantom and an anthropomorphic phantom. Results: When the flood field is acquired without the filter in place, a pixel gain artifact is clearly present in the image center which may be mis‐attributed to panel saturation in the subject image. At the image center, the artifact obscured all low contrast inserts and was also visible on the anthropomorphic phantom. Using the filter for flood field calibration eliminates the artifact. Conclusion: TrueBeams equipped with the 40 × 30 cm 2 IDU can utilize a modified flood field calibration procedure for FFF photon energies that improves image quality for cine MV imaging.